« Never Meet Your Heroes ». Généalogie cinématographique et matrice science-fictionnelle dans The Boys - Thomas Carrier-Lafleur; Baptiste Creps (ReS Futurae)
This article proposes to study The Boys (Prime Video, 2019-in production) from a genealogical approach that will shed light on the series' cinematic legacy, with a particular emphasis on its science fictional matrix. The starting point of this reflection lies in the paradigmatic shift embodied by The Boys, following the cinema of Zack Snyder (Watchmen, 2009 and Batman v Superman: Dawn of Justice, 2016), which consists in proposing a realistic rereading of the mythologies of the superhero, whose traditional model is thus strongly criticized, even deconstructed. Similarly, the authors will show how the use of the science- fictional imaginary, notably through the use of the film-matrix Scanners (David Cronenberg, 1981), composes a clear genealogical source while, at the same time, The Boys renews its relationship to cinephilic memory and to media and political criticism in a formal synthesis of New Hollywood.